Controlling timing and location in vaccines (2020)
Vaccines are one of the most powerful technologies supporting public health. The adaptive immune response induced by immunization arises following appropriate activation and differentiation of T and B cells in lymph nodes. Among many parameters impacting the resulting immune response, the presence of antigen and inflammatory cues for an appropriate temporal duration within the lymph nodes, and further within appropriate subcompartments of the lymph nodes– the right timing and location– play a critical role in shaping cellular and humoral immunity. Here we review recent advances in our understanding of how vaccine kinetics and biodistribution impact adaptive immunity, and the underlying immunological mechanisms that govern these responses. We discuss emerging approaches to engineer these properties for future vaccines, with a focus on subunit vaccines.